2013
DOI: 10.1007/s12010-013-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamic and Docking Interaction Study of Heterodera glycines Serine Proteinase with Vigna mungo Proteinase Inhibitor

Abstract: Many plants do produce various defense proteins like proteinase inhibitors (PIs) to protect them against various pests. PIs function as pseudosubstrates of digestive proteinase, which inhibits proteolysis in pests and leads to amino acid deficiency-based mortality. This work reports the structural interaction studies of serine proteinase of Heterodera glycines (SPHG) with Vigna mungo proteinase inhibitor (VMPI). 3D protein structure modeling, validation of SPHG and VMPI, and their putative protein-protein bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…This docking interaction analysis also confirmed the substrate binding groove of cHSP70. Such substrate binding groove in HSP70 and other proteins were reported earlier in other species [ 53 , 54 ]. Moreover, to confirm the presence of the above said active sites in other animal HSP70 protein expressed by HSPA1A gene, we performed MSA of 17 selected sequences ( S4 Fig ).…”
Section: Resultssupporting
confidence: 79%
“…This docking interaction analysis also confirmed the substrate binding groove of cHSP70. Such substrate binding groove in HSP70 and other proteins were reported earlier in other species [ 53 , 54 ]. Moreover, to confirm the presence of the above said active sites in other animal HSP70 protein expressed by HSPA1A gene, we performed MSA of 17 selected sequences ( S4 Fig ).…”
Section: Resultssupporting
confidence: 79%
“…Evaluation with VERIFY 3D indicated a reasonably good sequence-to-structure agreement as in crystal structure (Prasad, Gupta, Gaponenko, & Dhar, 2012). Similar validation study was also observed by Prasad et al, (Prasad, Gupta, Gaponenko & Tiwari, 2013). Moreover, a detailed secondary structural investigation of PfPP5 shows that structure folds into 13 Alfa-helices, 3 sheets, 14…”
Section: Generation Of Pfpp5 Modelsupporting
confidence: 82%
“…Moreover, PA works as a metabolite and play protective as other defensive roles in response to stress (Liu et al, 2015). Three transcripts encode nonspecific serine/threonine protein kinase enzyme (EC 2.7.11.1) which belongs to the family of transferases (Prasad et al, 2013; Gupta et al, 2015b). Generally, these enzymes are involved in plant response to abiotic stresses and abscisic acid (ABA)-dependent plant development through phosphorylation process (Kulik et al, 2011).…”
Section: Resultsmentioning
confidence: 99%